2019
DOI: 10.17770/sie2019vol1.3711
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of Student-Generated Questions in Disciplinary Reading Practices in Higher Education Environments

Abstract: The paper sets out to explore the issue of students’ strategic ability of learning from disciplinary texts in tertiary education settings. While performing reading tasks, students acquire or restructure subject-area knowledge as well as improving conceptual resources and literacy skills indispensable for their academic attainment. The so-called reciprocal reading instruction promotes the adoption of a procedure in which students are required to generate their own text-based questions, then ask and answer them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…As shown in Table 1, 89.4% of all the questions generated during the strategy training sessions and 96.2% asked in the delayed sessions fulfilled the criterion related to the clarity of questions. These findings are consistent with those the researchers obtained from their previous study investigating the use of the strategy of generating readers' own questions in reciprocal reading instruction at academic level (Chodkiewicz & Kiszczak, 2019). With regard to the second research question, the findings revealed that at the beginning of the study the participants struggled with posing linguistically correct questions.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As shown in Table 1, 89.4% of all the questions generated during the strategy training sessions and 96.2% asked in the delayed sessions fulfilled the criterion related to the clarity of questions. These findings are consistent with those the researchers obtained from their previous study investigating the use of the strategy of generating readers' own questions in reciprocal reading instruction at academic level (Chodkiewicz & Kiszczak, 2019). With regard to the second research question, the findings revealed that at the beginning of the study the participants struggled with posing linguistically correct questions.…”
Section: Resultssupporting
confidence: 90%
“…Such a view can be supported with reference to the results obtained in both the training and practice sessions, with explicit explanation and guidance provided by the teacher, and in the delayed sessions, when the students worked independently using the already practiced procedure. Generally, with the appropriately chosen difficulty level of content-area texts, as also shown by the results of this study and in Chodkiewicz and Kiszczak (2019), EFL students are capable of asking questions relevant to the content of texts, answerable and clear to the recipient, which undeniably shows that having understood the texts students are able to effectively address the text content in their questions.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations